The nonlinear relationship between corporate social responsibility disclosure and Islamic bank efficiency in GCC countries: the moderating role of audit quality - Chafai, Ahmed; Alsulami, Faizah (Cogent economics & finance, 2025)
Although the relationship between corporate social responsibility (CSR) and banking performance has been the subject of several articles, the non-linear relationship between CSR disclosure and banking efficiency remains less explored, specifically in the Islamic banking sector and notably in the Gulf Cooperation Council (GCC) region. Moreover, the moderating effect of audit quality (AUQ) on this relationship has not also been examined. This research aims to examine the nonlinear relationship between CSR disclosure CSR disclosure and Islamic bank efficiency (IBE) and analyses the moderating effect of AUQ in this relationship. To achieve this, a sample of 43 Islamic banks located in the six GCC countries is constructed over the period 2012–2020. The sample was selected based on the completeness and availability of CSR-related data. This ensured a standardized dataset to enhance the reliability of the results. To estimate this relationship, we used system GMM method, addressing endogeneity concerns like reverse causality, unobserved heterogeneity and dynamic panel bias. Contrary to alternative estimation techniques, this method uses internal instruments to correct for potential biases, thereby improving the robustness and precision of estimates in dynamic panel models. The results revealed that there is an inverted U-shaped relationship between CSR disclosure and IBE. Furthermore, AUQ moderates the link between CSR disclosure and IBE. The results suggest that the interaction between CSR and AUQ enhances IBE, but bank efficiency could be affected by weak AUQ. The results will be useful to policy makers and Islamic bank managers in the GCC countries by increasing the CSR disclosure.